(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research discusses the urgency of digital literacy and its challenges in the context of historical learning; in line with the rapidly growing use of technology and information, the ability to find sources of information that can be accounted for becomes an obligation that must be mastered by someone as a user of information sources. In the context of digital literacy, everyone needs the ability to conduct internet searches, guide hypertextdirection, evaluate informational content and prepare knowledge. The method used in this study is a qualitative descriptive method because the research conducted has a research subject that is part of social symptoms; the field situation is presented without being manipulated. The positive impact of the application of digital literacy in historical learning is: (1) helping the learning process; (2) maximizing its ability to think critically and creatively and have different thought patterns due to the absence of limitations in obtaining knowledge sources; (3) opening opportunities for teachers to be more productive in using digital technology in learning.